STRATEGI MANAJEMEN SOSIALISASI PENYELENGGARAAN HAJI DAN UMRAH PT FAJRI TOUR TRAVEL TANGERANG - Ahmad Rafiudin; Silvia Qurrotul Aini (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
The problems studied in this thesis are: How is the Umrah Jamaat Socialization Strategy carried out by Travel Indonesia PT. The purpose of this research is to find out the form of strategy in socializing with Umrah pilgrims at PT Fajri Tour Travel Tangerang. facts and data regarding the form of the Umrah Jama'at Socialization Strategy at PT Fajri Tour Travel Tangerang, then the data is described, analyzed and discussed to answer these problems. From the results of this study it was found that the strategy used by PT. Fajri Tour Travel Tangerang is an Intensive Strategy, which includes product development and increased product sales. This form of development is adapted to situations and conditions with a dynamic form, one of its characteristics is that marketing implementers can be creative according to the shape of the market they are facing. So with this dynamic form of development, it is also hoped that the increase in product sales has the opportunity to increase consumer acquisition from time to time. While the socialization process is carried out in collaboration with institutional parties, such as the taklim assembly, Islamic holidays and other events related to program socialization, and also always carries out socialization by providing good services, such as office services and when doing activities. socialization in agencies or institutions. Keywoard: Management, Travel, Socialization